Les régions, porteuses de nouveaux compromis pour l’agriculture ? - Aurélie Trouvé (Revue de la Régulation)
While the Common agricultural policy is deeply questioned, the rooms for manoeuvre of the regions are increasingly strengthened. Without any European stable compromise which answers to new social demands, do they are taken into account into regional policies, resulting from new compromises for agriculture ? To test this idea, power relations are analysed between three main types of divergent interests : neo-mercantilist, neo-liberal and multifunctional ones. Surveys on the field were realized in eight British, French and German regions. They show that the regionalisation leads to the institutionnalisation of different regional compromises. However, it seems to mainly reproduce the dominant power relations at the European level, the persistence of neomercantil interests, the hegemony of the neo-liberal ones and the lack of consideration of the multifonctional ones.